Propagation-Time-Consistent Ray-Path Correction for Long-Baseline Underwater Acoustic Localization - Zhichao Lv; Siyuan Wang; Libin Du; Gang Wang; Kaiyan Han; Fei Yu; Guoli Song (Journal of Marine Science and Engineering, 2026)
Non-uniform sound velocity profiles (SVPs) cause sound-ray refraction and propagation-path bending. The straight-line mapping among propagation time, propagation distance, and target position is, therefore, disrupted, leading to systematic errors in constant-sound-speed localization. To improve the consistency between propagation correction and geometric localization, an iterative ray-path correction method based on propagation-time consistency is proposed. The method contains three coupled steps. First, a path-dependent local layered SVP model is constructed for each target-to-base-station path, rather than using a global or fixed sound-speed model. Second, the ray parameter is inverted under the constraint of measured time-of-arrival (TOA), so that the corrected ray path remains consistent with the observed propagation time. Third, the corrected slant range obtained by layered ray tracing is fed back into a known-depth weighted least squares (WLS) localization model, forming a closed-loop position update. The method is evaluated through long-baseline (LBL) simulations with multiple SVPs and propagation geometries and is validated using measured TOA data and an observation-derived SVP. The simulation results show that sub-meter accuracy can be achieved under the tested TOA-noise conditions. In measured-data validation, the planar localization error is reduced from 4.6866 m to 0.1923 m. No divergence is observed in the tested small SVP-perturbation cases.

Integrative transcriptomic and bioinformatic analyses predict candidate EMT-related genes in sepsis-associated acute lung injury - Jun Liu; Yun Chen; Hao Peng; Zheyuan Xu; Yang Wang; Libin Zhang; Han Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Characterization of T5DL·5DS-2RS, a wheat-rye chromosomal translocation with enhanced grain hardness and pre-harvest sprouting resistance - Xin Liu; Huiting Zhang; Zhenglan Cao; Yanhong Lei; Mengyu Han; LiBin Wang; Yilong Dong; Jishan Niu; Yaping Cao; Jiajia Zhao; Jun Zheng; Xueming Yang; et al. (Theoretical and Applied Genetics, 2026)

Spatiotemporal variations in indoor thermal environments and dynamic comfort of passengers in airport terminals during winter - Yuxin Yang; Juan Yu; Deyin Zhang; Hao Tang; Wenzhong Jiang; Libin Han; Junmin Li; Borong Lin; Yu Dong (Building and Environment, 2026)

From morphology to metabolites: Integrated analysis of chemical and functional diversity in six shape-distinct premium green teas - Jia-Ping Ke; Guoping Lai; Chen Jiang; Shan Jiang; Xuedi Qin; Libin Chen; Tong Jia; Zisheng Han; Liang Zhang (Food Chemistry, 2025)

Sprayable and scalable superhydrophobic passive daytime radiative cooling coating for sub-ambient temperature regulation - Chengjie Qu; Qingqing Lu; Bo Wang; Jinyue Song; Ziye Han; Xingxiang Ji; Zuankai Wang; Libin Liu (Energy and Buildings, 2025)

Metabolomic insights into pigment and bioactive metabolite alterations in Eucommia ulmoides leaves: A comparison between new variety and wild-type varieties - Tiannuo Hong; Jiayu Gu; Lu Chen; Xiaolu Wang; Libin Zhou; Xuehu Li; Wenke Bai; Linqi Gao; Xiaodong Li; Guangming Zhao; Juan Han; Luxiang Liu (Food Chemistry, 2025)

Upper-critical-solution-temperature-type hydrogel smart window with wide temperature regulation for all weather privacy protection and energy saving - Hongzhi Liu; Chengjie Qu; Shuxian Song; Ziye Han; Xingxiang Ji; Ligang Gai; Libin Liu (Chemical Engineering Journal, 2025)

Instant-healing hydrogel-based triboelectric nanogenerator fornon-contact sensing and energy harvesting - Hao Zhang; Dongmei Li; Yajun Ren; Libin Han; Honghui Teng (Chemical Engineering Journal, 2025)

Regulating pH distribution of soda saline-alkali soil during electrochemical treatment by conditioning catholyte pH coupled with approaching anodes - Yinyin Zhang; Jiangtao Han; Changhui Luan; Yuyan Zhao; Sheng Xu; Qiaoqiao Wei; Libin Zang (Environmental Geochemistry and Health, 2025)

A novel g-C3N4/TiO2 heterojunction for ultrasensitive detection of bisphenol A residues - Xin Jiang; Han Jiang; Yimin Tang; Rui Wang; Wenxue Wang; Libin Yang; Bing Zhao (Food Chemistry, 2025)

MiR-23a promotes autophagy of yak cumulus cells to alleviate apoptosis via the apoptosis signal-regulating kinase 1/c-Jun N-terminal kinase pathway - Xiaohong Han; Sijiu Yu; Yan Cui; Jingjing Li; Jiangfeng Fan; Libin Wang; Meng Wang; Yangyang Pan; Gengquan Xu (Theriogenology, 2023)

Research on underwater acoustic field prediction method based on physics-informed neural network - Libin Du; Zhengkai Wang; Zhichao Lv; Lei Wang; Dongyue Han (Frontiers in Marine Science, 2023)
In the field of underwater acoustic field prediction, numerical simulation methods and machine learning techniques are two commonly used methods. However, the numerical simulation method requires grid division. The machine learning method can only sometimes analyze the physical significance of the model. To address these problems, this paper proposes an underwater acoustic field prediction method based on a physics-informed neural network (UAFP-PINN). Firstly, a loss function incorporating physical constraints is introduced, incorporating the Helmholtz equation that describes the characteristics of the underwater acoustic field. This loss function is a foundation for establishing the underwater acoustic field prediction model using a physics-informed neural network. The model takes the coordinate information of the acoustic field point as input and employs a fully connected deep neural network to output the predicted values of the coordinates. The predicted value is refined using the loss function with physical information, ensuring the trained model possesses clear physical significance. Finally, the proposed prediction model is analyzed and validated in two dimensions: the two-dimensional acoustic field and the three-dimensional acoustic field. The results show that the mean square error between the prediction and simulation values of the two-dimensional model is only 0.01. The proposed model can effectively predict the distribution of the two-dimensional underwater sound field, and the model can also predict the sound field in the three-dimensional space.

Cooperated catalytic mechanism of atomically dispersed binary Cu-N4 and Zn-N4 in N-doped carbon materials for promoting electrocatalytic CO2 reduction to CH4 - Cuihua An; Shuai Wu; Rui Huang; Xiaodong Chen; Xiaopeng Han; Hassanien Gomaa; Qibo Deng; Libin Zhao; Ning Hu (Chemical Engineering Journal, 2023)

Spatialization of Chinese R-410A emissions from the room air-conditioning sector - Pengcheng Wu; Li Zhang; Bo Yao; Bofeng Cai; Yifang Zhu; Hui Liu; Pengling Wang; Lisha Liu; Yanwei Dou; Han Yan; Yijun Liu; Zixuan Xie; et al. (Environment, Development and Sustainability, 2023)

Composition and indication of plankton fatty acids under the influence of environmental factors in the Hongfeng Reservoir, Southwest China - Xing Wang; Qiuhua Li; Wenshen Chen; Mengshu Han; Libin Han; Anton Brancelj (Aquatic Ecology, 2022)

The key environmental factors driving the succession of phytoplankton functional groups in Hongfeng Reservoir, southwest China - Libin Han; Qiuhua Li; Wensheng Chen; Xing Wang; Shihui Zhou; Mengshu Han; Anton Brancelj (Journal of Oceanology and Limnology, 2022)

Factors Affecting Operational Cost and Productivity of Ground-Based Timber Harvesting Machines: a Meta-analysis - Libin T. Louis; Anil Raj Kizha; Adam Daigneault; Han-Sup Han; Aaron Weiskittel (Current Forestry Reports, 2022)

Identification and testing of reference genes for Sesame gene expression analysis by quantitative real-time PCR - Libin Wei; Hongmei Miao; Ruihong Zhao; Xiuhua Han; Tide Zhang; Haiyang Zhang (Planta, 2013)